A direct arylation approach towards efficient small molecule organic solar cells. Issue 3 (16th December 2015) - Kudrjasova, Julija; Kesters, Jurgen; Verstappen, Pieter; Brebels, Jeroen; Vangerven, Tim; Cardinaletti, Ilaria; Drijkoningen, Jeroen; Penxten, Huguette; Manca, Jean; Lutsen, Laurence; Vanderzande, Dirk; Maes, Wouter
Abstract : Direct arylation affords organic semiconductors enabling high solar cell efficiency upon careful removal of the 'miss-coupled' side products. Abstract : Three extended molecular chromophores, differing in their central acceptor moiety and specifically designed as electron donor components for small molecule organic solar cells, are synthesized via a two-fold C–H arylation protocol. Upon removal of the side products inherent to the applied direct (hetero)arylation procedure, a record power conversion efficiency of 5.1% is achieved.